2018
DOI: 10.3310/hta22070
|View full text |Cite
|
Sign up to set email alerts
|

PET-PANC: multicentre prospective diagnostic accuracy and health economic analysis study of the impact of combined modality 18fluorine-2-fluoro-2-deoxy-d-glucose positron emission tomography with computed tomography scanning in the diagnosis and management of pancreatic cancer

Abstract: Background Pancreatic cancer diagnosis and staging can be difficult in 10–20% of patients. Positron emission tomography (PET)/computed tomography (CT) adds precise anatomical localisation to functional data. The use of PET/CT may add further value to the diagnosis and staging of pancreatic cancer. Objective To determine the incremental diagnostic accuracy and impact of PET/CT in addition to standard diagnostic work-up in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 72 publications
2
70
0
3
Order By: Relevance
“…PET–CT showed low accuracy in differentiating benign from malignant periampullary lesions in 57 per cent of patients, although it had a relatively good ability to detect lymph node metastasis. The recent PET‐PANC study showed similar sensitivity and specificity between multidetector CT and PET–CT. PET–CT upstaged disease, preventing resection in 11 per cent of patients.…”
Section: Discussionmentioning
confidence: 97%
“…PET–CT showed low accuracy in differentiating benign from malignant periampullary lesions in 57 per cent of patients, although it had a relatively good ability to detect lymph node metastasis. The recent PET‐PANC study showed similar sensitivity and specificity between multidetector CT and PET–CT. PET–CT upstaged disease, preventing resection in 11 per cent of patients.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the National Institute of Clinical Excellence (NICE) of the UK has recommended the use of PET‐CT in the routine staging of patients with resectable pancreatic cancer . Ghaneh et al . in a recent prospective study assessing the diagnostic accuracy and clinical value of PET‐CT in suspected pancreatic cancer patients have shown that the biggest impact of PET‐CT was on those patients who were identified as having resectable tumours on CT and who were then deemed not suitable for resection following PET‐CT.…”
Section: Discussionmentioning
confidence: 99%
“…The authors did not mention a group sequential design or adjustment of the type I error. Ghaneh et al applied an adaptive design for sample size reestimation based on the correlation between the test errors (false positives and false negatives) in a multicenter, prospective diagnostic accuracy study for the diagnosis of pancreatic cancer.…”
Section: Adaptive Designs For Diagnostic Accuracy Studiesmentioning
confidence: 99%